Teaching English in secondary schools in Sarawak, Malaysia: ESL teacher cognition perspectives / Willie Anak Jandar - Jandar, Willie (Institute of Graduate Studies, UiTM, 2017)
The main aim of this study was to explore teacher cognition in the context of instructional practice among English teachers in secondary schools in Samarahan division, Sarawak, Malaysia. Teacher cognition by Borg’s definition includes ‘what they know, believe, think and do’. In Borg’s schematic conceptualization of teacher cognition, it is illustrated that teacher cognition developed and is shaped by schooling and the professional education of the teacher. In the context of pedagogic practice, it is influenced and affected by contextual factors such as school environment, curricular, resources and students so much that it is not static but dynamic. Shulman outlined seven knowledge types to represent teacher cognition, but in this study only three knowledge domains/types namely, Knowledge of Students (KS), Pedagogical Content Knowledge (PCK) and General Pedagogical Knowledge (GPK) were deemed relevant to pedagogic practice. To address the main aim of the study, three research questions were posited namely, what are ESL teacher cognition perspectives?, what are the existing and new features of each knowledge domain?, and what are the similarities of KS, PCK and GPK of the four teacher participants?